Blurring the boundaries. University actorhood and institutional change in global higher education. Issue 4 (2nd October 2021) - Zapp, Mike; Marques, Marcelo; Powell, Justin J. W.
ABSTRACT: Higher education (HE) scholarship often focuses on the so-called 'entrepreneurial' university as a consequence of new public management reforms. Simultaneously, the remarkable expansion of private HE is said to fragment, specialize, and diversify HE systems. Such diagnoses are misleading as they ignore wider environmental pressures and simultaneous changes in both public, non-profit and for-profit HE. We argue that putative diversity in HE operates as a ceremonial façade behind which large-scale isomorphic change across national HE systems, sectors, and organizational forms occurs. Multiple causes trigger such change originating in the increasingly global HE environment, including a burgeoning international HE regime, accounting and accountability practices, increased permeability of HE systems facilitated by open borders, education markets, and global science as well as (neo)liberal ideologies stressing human capital and human rights. As other organizations, those in HE become subject to these pressures turning universities into more rationalized, standardized, and strategic actors.